1993
DOI: 10.1037/0735-7036.107.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Maternal contributions to sensory experience in the fetal and newborn rat (Rattus norvegicus).

Abstract: Using videographic analyses, we identified and quantified maternal contributions to the sensory environment of the perinatal rat (Rattus norvegicus) by analyzing, from the offspring's perspective, the dam's activities during gestation, labor, and delivery. Our observations indicate that pregnant females remain highly active during the final week of gestation, as compared with nonpregnant control animals. Exploratory movements, feeding, drinking, self-grooming, and other activities of the rat dam pitch, turn, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
48
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 49 publications
0
48
0
2
Order By: Relevance
“…There is now a general agreement that the fetus is exposed to considerable stimulation in utero and that maternal behavior and physiology contribute significantly to fetal experience (19)(20)(21)(22)(23). Studies to assess maternal activity in the rat during pregnancy have shown that fetuses are exposed to a dynamic series of different stimuli.…”
Section: Basic Sensory and Learning Capabilities Of The Fetus Animal mentioning
confidence: 99%
“…There is now a general agreement that the fetus is exposed to considerable stimulation in utero and that maternal behavior and physiology contribute significantly to fetal experience (19)(20)(21)(22)(23). Studies to assess maternal activity in the rat during pregnancy have shown that fetuses are exposed to a dynamic series of different stimuli.…”
Section: Basic Sensory and Learning Capabilities Of The Fetus Animal mentioning
confidence: 99%
“…Following delivery, there ensued a thermal regimen mimicking the natural sequence of postpartum temperature exposures within the nest (Alberts et al, 1991;Ronca et al, 1993), which typically involves evaporative cooling immediately after delivery and rewarming when the dam gathers and begins to brood the pups. Blood was collected at 0, 5, 30, 60, 90, or 120 min postpartum (hereafter referred to as T0, T5, T30, T60, T90, and T120); thus the amount of time pups spent at a given temperature depended on the temporal condition to which they were assigned.…”
Section: Postpartum Treatment Of Cesarean and Vaginally Delivered Pupsmentioning
confidence: 99%
“…We also found that simulated labor contractions more than double the likelihood that pups will first attach to the mother's nipple at 2 hr postpartum (Abel, Ronca, & Alberts, 1998) under thermal conditions mimicking the rat's natal environment in the laboratory setting (Alberts, Blumberg, & Ronca, 1991). Using remote video surveillance, we have described in detail the birth process in the rat from the offspring's perspective (Ronca, Lamkin, & Alberts, 1993). Behavioral expressions of labor are present 6 hr prior to the birth of the first pup.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to Earth-bound controls, we expected the flight dams to turn and rotate their bodies more frequently and in orientations that would be uncommon on Earth. The dams' behavior is biologically meaningful because their body movements create numerous episodes of angular acceleration that can be detected by fetuses and evoke responses from them (Ronca, Lamkin, & Alberts, 1993). We predicted neurovestibular and behavioral changes in offspring secondary to the pregnant dams' behavior in microgravity.…”
mentioning
confidence: 99%